English to Indonesian Translation of the Idiomatic Expressions Used in Confessions of an Ugly Stepsister Novel by Gregory Maguire - Melati, Widya Ardila; Muamaroh, Muamaroh (Applied Research on English Education (AREE), 2023)
This research focused at analyzing the type of idiomatic expressions found in the novel “Confessions of an Ugly Stepsister” and the translation strategies used to translate the idiomatic expressions. The aims of this research are to identify the types of idiomatic expressions and translation strategies used to translate the idioms found in the novel. This research used descriptive-qualitative method with expert opinions. To collect and analyze the data, researcher uses document analysis method. The researcher found 200 idiomatic expressions in the novel. To analyze the data, the researcher uses Fernando’s theory of idioms classifications and Baker’s theory of translation strategies. Based on the result, there are three types of idiomatic expressions: 76 pure idioms, 80 semi-idioms, and 44 literal idioms. Furthermore, there are three strategies used in translating the idiomatic words: 44 using an idiom of similar meaning and forms, 19 using an idiom of similar meaning but dissimilar form, and 137 paraphrase.